Process optimization of vacuum fried mango (Mangifera indica L. c.v. Indian) chips using response surface methodology - Navarro, Paula Dennixe D.C
This study aimed to optimize the process parameters of vacuum fried mango (Mangifera indica L. cv Indian) using response surface methodology. Specifically, the study (1) evaluated the effects of stage of ripeness of mango (Mangifera indica L. cv. Indian) and process parameters (time, temperature, and loading capacity) on the quality of vacuum fried mango (Mangifera indica L. cv. Indian) chips; and, (2) established and validated the optimized vacuum frying process parameters that include time (s), temperature (°C) and loading capacity (kg) on the quality of vacuum fried mango (Mangifera indica L. cv. Indian) chips. Indian mango at 3 days after harvest (80 Days After Flower Induction + 3 days after harvest) was chosen, based on logistics of procurement, storage time, ease of preparation and overall acceptability score, as the appropriate stage of ripeness used throughout the conduct of the study. Moreover, the generated statistical models accurately predicted the significant effects (p<0.05) of vacuum frying process parameters (time, temperature, and loading capacity) on the quality based on color L*, a*, and b* values, water activity (aw), moisture content (% dry basis), yield (%), and sensory acceptability (appearance, color, aroma, texture, flavor, and overall acceptability) of vacuum fried Indian mango chips. The optimum process parameter combination of 50 s frying time, 102°C frying temperature, and 2 kg loading capacity, with desirability index of 0.796, was established for vacuum frying Indian mango chips. Validation of the optimized vacuum frying process parameters (time, temperature, and loading capacity) showed that both, optimal and non-optimal vacuum fried Indian mango chips, fall within their respective % confidence (CI) and prediction intervals (PI) at significance level of α=0.05.